The resolved structure of a low-metallicity photodissociation region - Clark, Ilyse; Sandstrom, Karin; Wolfire, Mark; Bolatto, Alberto D.; Chastenet, Jérémy; Dale, Daniel A.; Gaches, Brandt A. L.; Glover, Simon; Goicoechea, Javier R.; Gordon, Karl D.; Groves, Brent; Hands, Lindsey; et al. (The astrophysical journal, 2025)
Photodissociation regions (PDRs) are key to understanding the feedback processes that shape interstellar matter in galaxies. One important type of PDR is the interface between H ii regions and molecular clouds, where far-ultraviolet radiation from massive stars heats gas and dissociates molecules. Photochemical models predict that as metallicity decreases, the C/CO transition occurs at greater depths in the PDR compared to the H/H2 transition, increasing the extent of CO-dark H2 gas in low-metallicity environments. This prediction has been difficult to test outside the Milky Way due to the lack of high-spatial-resolution observations tracing H2 and CO. This study examines a low-metallicity PDR in the N13 region of the Small Magellanic Cloud (SMC), where we spatially resolve the ionization front, the H2 dissociation front, and the C/CO transition using 12CO J = 2−1, 3−2, and [C I] 1-0 observations from the Atacama Large Millimeter/submillimeter Array and near-infrared spectroscopy of the H2 2.12 1-0 S(1) vibrational line, and H recombination lines from the James Webb Space Telescope. Our analysis shows that the separation between the H/H2 and C/CO boundaries is approximately 0.043 ± 0.013(stat.) ± 0.0036(syst.) pc (equivalent to at the SMC’s distance of 62 kpc), defining the spatial extent of the CO-dark H2 region. Compared to our plane-parallel PDR models, we find that a constant-pressure model matches the observed structure better than a constant-density one. Overall, we find that the PDR model does well at predicting the extent of the CO-dark H2 layer in N13. This study represents the first resolved benchmark for low-metallicity PDRs.
Online verfügbar: 09. September 2025
Gesehen am 05.02.2026